POLITICAL AND ECONOMIC CONTEXT OF SIGNING SOVIET-BRITISH TRADE AGREEMENT - A. V. Majgur (Гуманитарные и юридические исследования)
With the reference to published documents and published historical data the article gives a brief outline as regards the history of signing the Soviet-British trade agreement. Particular attention is paid to the activities of the two countries on the path to a compromise solution. The article concludes that in spite of their mutual interest in the conclusion of a package of trade agreements the United Kingdom made the government cancel the contract due to power struggle in the parliament. It resulted in deterioration of relations with Russia up to the present time.